Self-assessment Optimization Through WhatsApp Features for Increasing Students' Listening Comprehension - Syamsiah Depalina Siregar; Eka Melati; Sri Wahyuni (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2021)
The article is aimed to inform that self-assessment optimization through WhatsApp features can Increase the students’ listening comprehension. The action research is used to gain the data. It consists of 4 steps, like planning, acting, developing, and reflecting stage. It conducted for two cycles. The informants of this research come from fourth semester of English Education Program at STAIN Mandailing Natal. The instruments of collecting the data are an interview guide, online questionnaire, Listening script, and field note. Qualitative and quantitative data were analyzed in this analysis. Qualitative data would be collected by observation, interviewing, and surveying. The listening examination will collect quantitative evidence. It will be evaluated using a listening comprehension score calculation. The result of the research showed the increasing on students’ listening comprehension through self-assessment optimization, it can be seen from the students’ scoring in each meeting.